1998
DOI: 10.1111/j.1600-0404.1998.tb07290.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous intracranial hematomas: role of dynamic CT and angiography

Abstract: Forty-five patients with spontaneous intracerebral hemorrhage (ICH) were studied prospectively by dynamic CT and cerebral angiography. The accuracy of dynamic CT in demonstrating the underlying vascular cause in ICH was evaluated. Dynamic CT correctly predicted 90% of aneurysms, 83% of AVMs and 100% of normal studies as compared to angiography. Cerebral angiography can be obviated in patients where dynamic CT does not show any obvious vascular anomaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…We confirmed 16 patients of vascular abnormalities with additional studies and the findings were compatible. Therefore, 3D-CTA manifested as a highly sensitive modality in our study as reported elsewhere 3,8,23) .…”
Section: Discussionsupporting
confidence: 64%
“…We confirmed 16 patients of vascular abnormalities with additional studies and the findings were compatible. Therefore, 3D-CTA manifested as a highly sensitive modality in our study as reported elsewhere 3,8,23) .…”
Section: Discussionsupporting
confidence: 64%
“…In the present study, hypertensive patients over the age of 60 (n = 21) underwent only CTA or MRA due to the invasive nature of catheter angiography. The diagnostic yield of CTA and MRA for detecting vascular abnormalities in patients with ICHs was not inferior to that of catheter angiography [10, 11]. Nonetheless, it might have led to an underestimation of angiographic abnormalities in the group, although not considerable.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,[12][13][14][15][16][17][18][19][20][21] Some of these studies contributed to the total of 726 patients with ICH in whom it was possible to calculate the yield of IADSA for finding an aneurysm or arteriovenous malformation (AVM) as the cause of the ICH. [3][4][5]14,17,18,21,25,28 The prevalence of underlying AVMs was 20% (95% CI, 17 to 23) and of aneurysms, 13% (95% CI, 11 to 16; Table 1). Sex of the patients did not appear to influence yield in the individual studies, but the pooled results showed that the yield was relatively low in patients with prestroke hypertension and in those with a deep ICH location ( Table 1).…”
Section: Yield Of 1 Investigationmentioning
confidence: 99%
“…27 The 4 remaining studies compared DSA-MRA against IADSA (11 patients with ICH; no false-positives or false-negatives), 28 3-dimensional CT angiography against IADSA (31 patients with hyperacute ICH; no false-positives or false-negatives), 26 3-dimensional CT angiography against surgical findings (61 patients with massive, acute ICH requiring surgical decompression; sensitivityϭ55%, 95% CI, 38 to 71; specificityϭ97%, 95% CI, 83 to 99; positive predictive valueϭ94%, 95% CI, 74 to 99; and negative predictive valueϭ67%, 95% CI, 53 to 80), 24 and "dynamic" CT angiography against IADSA (44 patients with spontaneous lobar ICH; sensitivityϭ88%, 95% CI, 69 to 96; specificityϭ95%, 95% CI, 76 to 99; positive predictive valueϭ95%, 95% CI, 78 to 99; and negative predictive valueϭ86%, 95% CI, 66 to 95). 25 …”
Section: Diagnostic Utility Of Radiological Techniquesmentioning
confidence: 99%
See 1 more Smart Citation